Comparison of transrectal and transperineal prostate biopsy: a prospective comparative study - Vladimir A. Vorobev; Gadir R. Akperov; Olga V. Baklanova; Dmitry S. Mickevich; Egor V. Kovalev; Ivan P. Popov; Zahir S. Azizov (Consilium Medicum)
Background. Transrectal (TR) prostate biopsy remains the ”gold standard” but is associated with infectious risks; transperineal (TP) biopsy is considered a safer alternative with comparable diagnostic accuracy.